Niki Passath : thinking like a machine : an artists journey into robotics - Passath, Niki, 1977-; Bast, Gerald (Berlin : De Gruyter, 2017)
In many modes of behavior, people act more and more like machines. In the context of work, people have become a human resource that can be replaced at any time. An existence without purpose cannot be imagined ? just as a machine without function is absurd. Do humans already think like machines? Do they have a "master-slave" relationship with them? Are humans no longer any more than an organic prosthetic fitted to an inorganic body? With his created robotic beings, Niki Passath breaks with this seemingly rational technological system. By eliminating the predominant rationality of the machine, he gives it a new meaning. This book is the first monograph on the artist?s oeuvre. Internationally renowned experts shed light on the many facets of his work.
Includes bibliographical references.
Keywords: Passath, Niki, -- 1977-; Passath, Niki, -- 1977- -- Interviews; Robots in art